FACTORS INFLUENCE THE INTENTION TO USE IN PAYLATER FEATURE AMONG THE MILLENNIAL GENERATION - Kholidah Azzahra; Mardinawati Mardinawati; Sri Rahayu Zees; Prima Ayundyayasti (Politeknik Negeri Semarang, 2023)
These days the use of PayLater has become a trend in society, focusing on the gen z and millennials. This is because digital adoption in significantly higher than the previous generation. Shopee introduced the latest digital credit card payment feature called Shopee PayLater (SPayLater). In this case, the research is carried out on Acceptance and Use Technology in Shopee PayLater feature using UTAUT2 Model. This research aims to analyze the factors that influence the intention to use the PayLater feature on Shopee PayLater using UTAUT2 Model. The data used was obtained from distributing questionnaires with 122 respondents of millennial generation Shopee PayLater users. The data collection technique used is Nonprobability Sampling. The data was processed using SmartPLS 3. The resuts of this study indicate that there are variables that have a significant and no significant effect on the use of Shopee PayLater. The variables of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Price Value have no significant effect on Behavioral Intention. In addition, the Hedonic Motivation and Habit variables have a significant effect on the Behavioral Intention of using SPayLater. Another result of this research is that Behavioral Intention, Facilitating Conditions, and Habit variables have a significant effect on Use Behavior using Shopee PayLater.